4′, 7-Di-O-methylnaringenin (DMNG), a naringenin derivative, activates p53 signal pathway through down-regulating MDM2. (February 2022) - Zhang, Siyu; Wang, Yifan; Sun, Yujie; Zhao, Guangjian; Wang, Juan; Liu, Lu; Liu, Fang; Wang, Peng; Xu, Ximing
Graphical abstract: Highlights: DMNG is a potential p53 signaling activator. DMNG inhibits HCT-116 cells proliferation via arresting the progression of G2/M cell cycle and inducing apoptosis. DMNG is unable to cause DNA damage, and also cannot induce ROS stress. DMNG activates p53 signal pathway through down-regulating MDM2. Abstract: Naringenin, a citrus flavonoid that possessed various biological activities, had emerged as a potential therapeutic agent for the management of a variety of diseases, but naringenin derivatives' application in cancer therapy and underlying mechanisms of action were not fully understood. Our recent work had shown that 4′, 7-Di-O-methylnaringenin (DMNG) exerted its anti-colon cancer activity and the underlying mechanisms of action. We reported that DMNG could activate p53 signal pathway, dependent of p53 wild type status. We observed that DMNG decreased the survival of HCT-116 cells by induction of apoptosis and G2/M phase arrest. We further demonstrated that, in a dose- and time-dependent manner, DMNG effectively downregulated the MDM2 protein expression at protein translation level. Hence, our study unearthed that DMNG was a potential therapeutic and anti-metastatic agent for human colon cancer through down-regulating MDM2 and activating p53 pathway.